(untitled) (Research, Society and Development, 2022)
Forensic dentistry, or dentistry employed in the process that defines the identity of an individual, is an extraordinary tool in the technique of establishing the characteristics of a person when bodies are in an advanced stage of decomposition, fragmented or even charred, which makes it impossible to recognize them by examination. visual. Different methods for identification are available for the forensic dentist to use, from DNA analysis, molecular techniques, photographs or radiographic images. Objective: To present the main methods used in human identification within forensic dentistry. Methodology: This work is a qualitative literature review, which used the terms that give greater specificity to the search performed, terms such as: “legal dentistry” AND “cadaver” AND “dental arch”. The articles, published in the last 10 (ten) years (2012 to 2022), were obtained from the Scielo, Lilacs, PubMed and Google Scholar databases. Results: A total of 18 articles were analyzed in order to allow researchers to identify the different methods used to identify bodies. Conclusion: The use of radiographic image was the most used technique, but the need for previous images of the individual, indicates that this may not be the most effective where these records do not exist. An important fact was detected: the lack of specialized professionals in the area, causing slowness and compromise of the procedures used in the identification.